Determination of a novel ACE inhibitor in the presence of alkaline and oxidative degradation products using smart spectrophotometric and chemometric methods - Maha Abdel-Monem Hegazy; Maya Shaaban Eissa; Osama Ibrahim Abd El-Sattar; Mohamed Mohamed Abd El-Kawy (Elsevier, 2014)
Simple, accurate, sensitive and validated UV spectrophotometric and chemometric methods were developed for the determination of imidapril hydrochloride (IMD) in the presence of both its alkaline (AKN) and oxidative (OXI) degradation products and in its pharmaceutical formulation. Method A is the fourth derivative spectra (D4) which allows the determination of IMD in the presence of both AKN and OXD, in pure form and in tablets by measuring the peak amplitude at 243.0Â nm. Methods B, C and D, manipulating ratio spectra, were also developed. Method B is the double divisorâratio difference spectrophotometric one (DDâRD) by computing the difference between the amplitudes of IMD ratio spectra at 232 and 256.3Â nm. Method C is the double divisor-first derivative of ratio spectra method (DDâDR1) at 243.2Â nm, while method D is the mean centering of ratio spectra (MCR) at 288.0Â nm. Methods A, B, C and D could successfully determine IMD in a concentration range of 4.0â32.0Â Âµg/mL. Methods E and F are principal component regression (PCR) and partial least-squares (PLS), respectively, for the simultaneous determination of IMD in the presence of both AKN and OXI, in pure form and in its tablets. The developed methods have the advantage of simultaneous determination of the cited components without any pre-treatment. The accuracy, precision and linearity ranges of the developed methods were determined. The results obtained were statistically compared with those of a reported HPLC method, and there was no significant difference between the proposed methods and the reported method regarding both accuracy and precision. Keywords: Double divisorâratio difference, Double divisorâratio derivative, Mean centering of ratio spectra, Chemometry, Imidapril hydrochloride